Children’s agency in accessing for spaces of play in an urban high-rise community in Malaysia - Agha, Sharifah Shazana; Thambiah, Shanthi; Chakraborty, Kabita (Taylor & Francis, 2019)
This research explores children’s agency in negotiating for play spaces in Malaysia within the context of an urban high-rise community. Fieldwork was conducted with 31 children between the ages of four to 12 years old. A qualitative, child-centered approach to data collection was employed using participatory research methods. The study reveals how children gain access to play spaces and details their innovative strategies in maximizing play opportunities in a community with limited infrastructural and social support. It highlights how children claim the use of communal spaces within the housing compound, reinvent designated play spaces, resist adult rules around restricted spaces and embrace elements of global culture for meaningful play opportunities. The paper argues that children exercise agency in accessing play spaces, and by so doing, extend and expand their lived geographies which are not just spatial, temporal and social but also invented and imagined. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.